Clinical Pharmacy and Pharmaceutical Care: Patient-Oriented Application of Pharmaceutical Expertise - Markus L. Lampert; Stephan Krähenbühl; Kurt E. Hersberger; Raymond G. Schlienger (CHIMIA, 2006)
Clinical Pharmacy is a health speciality describing the activities and services of the clinical pharmacist to develop and promote the rational and appropriate use of drugs, medicinal products, and devices by the individual as well as by the society. Very closely related to the term of clinical pharmacy is the concept of pharmaceutical care. This means a new pharmacy practice paradigm which puts the patient into the centre. In the course of this practice, a pharmacist takes responsibility for a patient's drug-related needs with the aim of achieving definite outcomes that improve a patient's quality of life. At the University of Basel, clinical pharmacy and pharmaceutical care have developed constantly over the last twenty years. Examples from research and practice are given in this article, and areas for future work are outlined.